Developing Cognition Endpoints for the CENTER-TBI Neuropsychological Test Battery - Stenberg, Jonas; Karr, Justin E.; Terry, Douglas P.; Saksvik, Simen B.; Vik, Anne; Skandsen, Toril; Silverberg, Noah D.; Iverson, Grant L. (Frontiers in Neurology, 2020)
Background: Measuring cognitive functioning is common in traumatic brain injury (TBI) research, but no universally accepted method for combining several neuropsychological test scores into composite, or summary, scores exists. This study examined several possible composite scores for the test battery used in the large-scale study Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI). Methods: Participants with mild TBI (n=140), orthopedic trauma (n=72), and healthy community controls (n=70) from the Trondheim MTBI follow-up study completed the CENTER-TBI test battery at two weeks after injury, which includes both traditional paper-and-pencil tests and tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Seven composite scores were calculated for the paper and pencil tests, the CANTAB tests, and all tests combined (i.e., 21 composites): the overall test battery mean (OTBM); global deficit score (GDS); neuropsychological deficit score-weighted (NDS-W); low score composite (LSC); and the number of scores ≤5th percentile, ≤16th percentile, or <50th percentile. Results: The OTBM and the number of scores <50th percentile composites had distributional characteristics approaching a normal distribution. The other composites were in general highly skewed and zero-inflated. When the MTBI group, the trauma control group, and the community control group were compared, effect sizes were negligible to small for all composites. Subgroups with versus without loss of consciousness at the time of injury did not differ on the composite scores and neither did subgroups with complicated versus uncomplicated MTBIs. Intercorrelations were high within the paper-and-pencil composites, the CANTAB composites, and the combined composites and lower between the paper-and-pencil composites and the CANTAB composites. Conclusion: None of the composites revealed significant differences between participants with MTBI and the two control groups. Some of the composite scores were highly correlated and may be redundant. Additional research on patients with moderate to severe TBIs is needed to determine which scores are most appropriate for TBI clinical trials.